Anti-inflammatory activities of a new VEGF blocker, Conbercept. (3rd September 2021) - Liu, Yang; Fu, Hua; Zuo, Li
Abstract: Background: Angiogenesis and inflammation exhibit a mutually reinforcing relationship in many human diseases. Vascular endothelial growth factor (VEGF) is one of the most important proangiogenic mediators. Conbercept is a novel VEGF inhibitor. Method: Type II collagen-induced rat rheumatoid arthritis (CIA) model was established to evaluate the anti-chronic inflammation activities of Conbercept. ELISA was used to measure the concentrations of immune factors in the blood of arthritis rats. The xylene-induced ear edema was conducted to evaluate the effect of Conbercept on acute inflammation. Result and discussion: Our results showed that Conbercept significantly reduced the paw edema volume and the arthritis index in CIA rats. Furthermore, we found that Conbercept decreased the serum levels of vascular endothelial growth factor (VEGF), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) in CIA rats. Xylene-induced ear edema is a widely used method to study acute inflammation. Conbercept significantly inhibited xylene-induced ear edema. Conclusion: All results indicate that Conbercept exhibits significant inhibition of acute and chronic inflammation.